Increase of Organic Carbon Pool in Reclaimed Soils under Forest Stand - Gruszczyński, Stanisław; Sroka, Katarzyna; Wojtanowicz, Piotr (Geomatics and Environmental Engineering, 2019)
This paper contains the results of the studies on the content of organic carbon in the initial soils formed from soilless formations reclaimed for forest management. The obtained data allowed for the assessment of the carbon resources in the organic layer and in the mineral layers close to the surface. It also allowed us to make models that enabled us to determine the main factors influencing the rate of the increase. The strongest influence on the carbon sequestration during the forest reclamation of soilless formations has their lithology (granulation) and species composition of the planted trees. The time and situation (on a slope or a horizontal surface) are less important. The calculated annual increase of carbon indicates that the period necessary to store carbon in reclaimed soils in the quantities similar to the ones occurring in the soils of a natural forest is more than 100 years.